2018
DOI: 10.1016/j.bbamcr.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of sphingomyelin synthase 1 activity induces collecting duct cells to lose their epithelial phenotype

Abstract: Epithelial tissue requires that cells attach to each other and to the extracellular matrix by the assembly of adherens junctions (AJ) and focal adhesions (FA) respectively. We have previously shown that, in renal papillary collecting duct (CD) cells, both AJ and FA are located in sphingomyelin (SM)-enriched plasma membrane microdomains. In the present work, we investigated the involvement of SM metabolism in the preservation of the epithelial cell phenotype and tissue organization. To this end, primary culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 76 publications
3
10
0
Order By: Relevance
“…Anyway, it is known that an increase in mRNA quantity does not always translate into an increase in protein. Taking into account our present and past results (Brandán et al,2018; Favale et al,2015; Márquez et al,2012), we propose that the synthesis of SM is necessary to maintain the epithelial characteristics of the CD cells and that the decrease in SM induces mesenchymalization during aging.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Anyway, it is known that an increase in mRNA quantity does not always translate into an increase in protein. Taking into account our present and past results (Brandán et al,2018; Favale et al,2015; Márquez et al,2012), we propose that the synthesis of SM is necessary to maintain the epithelial characteristics of the CD cells and that the decrease in SM induces mesenchymalization during aging.…”
Section: Discussionsupporting
confidence: 69%
“…More recently, we demonstrated that the intracellular synthesis of SM is a requirement for the acquisition of mature AJ, necessary to preserve the tissue organization and the differentiated epithelial phenotype of MDCK cells, a cell line of dog kidney CD (Favale et al,2015). We further reported that the inhibition of SMS1, but not SMS2, altered intercellular adhesions in cultured renal papillary CD cells from young rats (Brandán et al,2018). Li et al (2007) reported that the downregulation of the two SMS isoforms alters the amount of SM exclusively in the plasma membrane raft domains of HEK 293 cells.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Although SMS1 deficiency in macrophages showed similar anti-atherosclerotic effects in a mice model [ 36 ], SMS1 is indeed not an appropriate therapeutic target. To date, it has been reported that SMS1 −/− mice exhibited several severe abnormalities, including defective insulin secretion [ 37 ], progressive hearing loss at a low frequency range [ 38 ], CD4 + T-cell dysfunction [ 39 ], adipocyte lipid storage dysfunction [ 40 ], male spermatogenesis defects [ 41 ], and mesenchymal transition of epithelial cells derived from the renal papillary collecting duct [ 42 ]. Disruption of SMSr in mice resulted in marginal changes in the plasma levels of sphingomyelin, ceramide, and S1P [ 43 , 44 ].…”
Section: Sphingomyelins and Atherosclerosismentioning
confidence: 99%